Biochemical Changes During Salt Fermentation of Pangasius hypophthalmus (Sauvage, 1878) - Praveen Kumar, G.; Balange, A. K.; Martin Xavier, K. A.; Nayak, B. B.; Sanath Kumar, H. (Fishery Technology, 2017)
The suitability of Pangasius hypophthalmus as a rawmaterial for salt fermentation and changes during135 days was analysed. Pangasius steaks werefermented in food grade PVC jar and biochemicalparameters such as pH, salt, thiobarbutric acidreactive substances (TBARS), free Î±-amino nitrogen(FAN), moisture and ash content were analysed. Themoisture content of Pangasius had shown a slightincrease during fermentation from 54.9% (0th day)to 56.67 (135th day). Ash content recorded anincrease from 11.98% on 1st day to 18.17% (135thday). Salt content of Pangasius steaks has increasedsignificantly (p0.5) during fermentation. TBARScontent recorded an increase till 75th day anddecreased continuously till maturation. The FANregistered an increase from 44.71 mg% (0th day) to92.86 mg% (135th day).The moisture, pH, ash, salt,TBARS, FAN in the final matured fermentedproduct were 56.67%, 5.93%, 18.17%, 14.43% and0.21 mg malonaldehyde kg-1 of fat and 92.86 mg%respectively. Therefore, it was concluded thatPangasius developed a firm consistency and characteristicflavour and taste over 135 days of maturation.